Pengaruh Tingkat Penambahan Daun Pepaya (Carica papaya L) Terhadap Karakteristik Nugget Ikan Lele - Rizki Fadhillah Lubis; Rahmad Syukur Siregar (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2017)
The purpose of this study was to determine the rate of addition of papaya right to characteristic of catfish nuggets. The design used was completely randomized design (CRD) with 4 treatments and 3 replications. Then do the analysis of variance, followed by Duncan's test New Multiple Range Test (DNMRT) on the real level of 5%. The treatment used is the addition of papaya leaves ranging from 0 g (A), 5 g (B), 10 g (C) and 15 g (D) into 100 grams of material. Data were collected for catfish nugget products include: moisture content, ash content, protein content, crude fiber content, fat content, oil absorption power, identification of alkaloids, β-carotene content, physical analysis, total plate test and organoleptic (color, aroma , taste and texture).The results showed that the addition of 10 grams of papaya leaves are still acceptable to the percentage of panelists who expressed love to really like the color as much as 95%, 85% aroma, flavor and texture of 65% to 80%. Chemical analysis of water content obtained 53.37%, ash content 1.41%, 12.22% protein content; levels of fat before frying 1.88%; levels of fat after frying 9.01%, 2.15% crude fiber; power oil absorption 7.13%; identification alkaloid (+ +); β-carotene content before frying 1993.2201 microg; once fried 1089.0280 microg; violence before frying 3.99 N / cm ², and after frying 2.71 N / cm ² and the plates a total of 1.1 x 104 CFU / g. Keywords: papaya leaves, nugget, catfish, β-carotene and alkaloids